The impact and management of recent drought on the West Bank groundwater aquifer system - Froukh L. (Economics of drought and drought preparedness in a climate change context, 2010)
Water is a vital element for the development of all sectors in Palestine. Currently, the estimated average per capita use is around 50 l per day, which is half of the minimum recommended by the World Health Organization (WHO). Water demand in the West Bank is expected to increase substantially in the future. This is due to improved standards of living and increased population growth rate. For example, the estimated domestic water demand for the West Bank in the year 2000 is around 98 million cubic meters (MCM) while it is currently in the range of 55 MCM/year. Projected water demand for the year 2020 for domestic purposes is around 278 MCM. To meet the demand for water, additional supply will be needed. Groundwater is the only source for water supply in the West Bank. Currently, most of the water from West Bank aquifers is utilized by the Israelis and only very limited amount is given to Palestinian for water supply in the Palestinian areas. The total amount currently extracted by the Palestinians and Israelis from the Eastern Basin is around 40 MCM/year. The West Bank has a Mediterranean climate. The annual average rainfall varies between 700-850 mm on the western slopes, 500 and 800 mm in the hilly areas and 100 to 150 mm in the Jordan Valley. Evaporation is particularly high in the summer due to a rise in temperature, intensive sunshine and low humidity. Rainfall is the only source for recharging aquifer systems in the West Bank. Recently, West Bank suffered severe droughts due to drop in the rainfall. As a result a significant drop in the water table in both the upper and lower aquifer systems which form the main source for water supply. This paper will investigate the impact of recent drought on the groundwater aquifer system in the West Bank and drought management procedures applied by Palestinian Water Authority in the light of continuous Israeli control of Palestinian aquifers.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)